A Green Star Fading? A Critical Assessment of Swedish Environmental Policy Change. (14th March 2014) - Hysing, Erik
ABSTRACT Frontrunner states have been shown to be highly important for the development and diffusion of progressive environmental policies. History shows, however, that frontrunner status is dynamic and that previous leader countries have become laggards. Here I assess recent policy changes in Sweden – a state widely recognized as an environmental frontrunner – arguing that environmental policy practice within areas prioritized by the Government (biodiversity, sustainable energy, the marine environment and climate change) has experienced high‐profile, and from a green perspective highly controversial policy changes. This policy development raises critical concerns for the future role of Sweden as an environmental frontrunner. Copyright © 2014 John Wiley & Sons, Ltd and ERP Environment